Color Symbolism in the Castilian Atlantic Bibles: Initials and Scenes from the Bible of Avila (BNM, Vit. 15-1) - Maria Rodriguez Velasco (Ignatianum University Press, 2020)
The Atlantic Bibles of the Umbro-Roman school are associated with the needs of the Gregorian Reform, which began at the end of the 11th century. Their first impression is one of great ornamental sobriety, in accordance with the early stages of what Garrison and Berg have labelled the "geometric style." This was first manifested in the decoration we find concentrated in the initials heading the individual books of the Bible. In Castile, one outstanding example is the Bible of Avila, begun by the Umbro-Roman school and finished in a Castilian scriptorium. This double perspective can be observed in a similarly double palette of color: Italian and Spanish. It is especially in this second phase when a reduction to the minimum of polychromy leads us to think that color has here a symbolic use. Red and blue, having had symbolic connotations since the birth of Christian iconography, are the principal colors of the scenes illustrated in the Bible of Avila, with the addition of green and yellow, which are also rich with symbolism. This possible symbolism of color may work to reinforce the conceptual nature of these miniatures, in direct relation to the text they decorate and to the liturgy they accompany. The Bible in the Middle Ages, in the context of monastic schools, was the most important manuscript for teaching and learning. Its miniatures and the symbolism of its colors contribute to the transmission of meanings.